Dampak Cuaca Terhadap Quality of Service Wireless pada Sistem First Person View - Agus Suhendar (Jurnal Manajemen Informatika (JAMIKA), 2021)
Streaming is the process of sending data continuously or continuously that be broadcast over the internet. FPV (First-person view) is a method used to control radio control vehicles from the pilot. Analysis of live video streaming service on FPV aeromodelling with standard configurations to determine the maximum results for live video streaming service on FPV aeromodelling. Distance measurements and environmental conditions are also necessary to determine the performance of live video streaming. Then performed a Quality of Service (QoS) analysis, including measurement of delay, jitter, and throughput using Wireshark. From the tests that have been carried out, the comparison of the best value between the measurement of data delay with a value of 0.0085 ms, for a jitter of 20.294 ms and throughput of 0.009 ms is obtained, all of which are in accordance with the standards recommended by ITU-T, so that the overall QoS obtained gives sufficient results.satisfying.